Age dependence of modern clinical risk groups for localized prostate cancer—A population‐based study. Issue 8 (3rd January 2020) - Huynh‐Le, Minh‐Phuong; Myklebust, Tor Åge; Feng, Christine H.; Karunamuni, Roshan; Johannesen, Tom Børge; Dale, Anders M.; Andreassen, Ole A.; Seibert, Tyler M.
Abstract : Background: Optimal prostate cancer (PCa) screening strategies will focus on men likely to have potentially lethal disease. Age‐specific incidence rates (ASIRs) by modern clinical risk groups could inform risk stratification efforts for screening. Methods: This cross‐sectional population study identified all men diagnosed with PCa in Norway from 2014 to 2017 (n = 20, 356). Age, Gleason score (primary plus secondary), and clinical stage were extracted. Patients were assigned to clinical risk groups: low, favorable intermediate, unfavorable intermediate, high, regional, and metastatic. Chi‐square tests analyzed the independence of Gleason scores and modern PCa risk groups with age. ASIRs for each risk group were calculated as the product of Norwegian ASIRs for all PCa and the proportions observed for each risk category. Results: Older age was significantly associated with a higher Gleason score and more advanced disease. The percentages of men with Gleason 8 to 10 disease among men aged 55 to 59, 65 to 69, 75 to 79, and 85 to 89 years were 16.5%, 23.4%, 37.2%, and 59.9%, respectively ( P  < .001); the percentages of men in the same age groups with at least high‐risk disease were 29.3%, 39.1%, 60.4%, and 90.6%, respectively ( P  < .001). The maximum ASIRs (per 100, 000 men) for low‐risk, favorable intermediate‐risk, unfavorable intermediate‐risk, high‐risk, regional, and metastatic disease were 157.1 for those aged 65 to 69 years, 183.8 for those aged 65 to 69 years, 194.8 for those aged 70 to 74 years, 408.3 for those aged 75 to 79 years, 159.7 for those aged ≥85 years, and 314.0 for those aged ≥85 years, respectively. At the ages of 75 to 79 years, the ASIR of high‐risk disease was approximately 6 times greater than the ASIR at 55 to 59 years. Conclusions: The risk of clinically significant localized PCa increases with age. Healthy older men may benefit from screening. Abstract : In a population‐based study of 20, 356 Norwegian men with prostate cancer, both the proportion and absolute incidence rate of advanced disease increase with age. At the ages of 75 to 79 years, the absolute incidence of high‐risk disease is 6 times greater than the incidence at the ages of 55 to 59 years, and this suggests that healthy older men may benefit from prostate cancer screening.